Wireless‐powered CR‐IoT with ambient backscattering: a new transmission mode. Issue 22 (16th February 2021) - Sun, Mengwei; Ding, Yuan; Goussetis, George
Abstract : In this study, a new hybrid secondary transmitter (ST) mode is proposed for cognitive radio Internet of Things (CR‐IoT) networks with energy harvesting (EH) and ambient backscatter (AmBack) communication capabilities. The authors firstly describe the proposed hybrid mode with wireless‐powered ST. The ST, consisting of EH, Amback, and conventional active transmission modules, adapts itself under different primary user operation states, i.e. active or idle. The overall throughput of the secondary system is formulated and the system settings for achieving optimal performance are derived and validated through numerical simulations.